Hubungan Tabernakel dengan Liturgi Ibadah bagi Iman Orang Percaya - Palit, Hano Abdinasti; Senduk, Hendy (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: The tabernacle is the tent of meeting or holy tabernacle that God commanded Moses to build as a place for God to dwell among His people, fellowship and communicate with His people. Today, believers become God's dwelling place so that the holy God is present among His people. The tabernacle refers to a pattern of worship determined by God and even a pattern for the growth of believers' faith. The method used is qualitative. The purpose of this research is to find out what is meant by the tabernacle in relation to the worship liturgy and its impact and growth of faith according to the spiritualized tabernacle. The results of the analysis and study show that worship patterned on the tabernacle will be realized by the Holy Spirit through the gifts of the Holy Spirit. The conclusion of this research is that: worship patterned in the tabernacle will motivate to increase the growth of the congregation's faith, the pastor will increasingly believe in his calling and there will still be manifestations of the Holy Spirit through the gifts of the Holy Spirit.Abstrak: Tabernakel adalah kemah pertemuan atau kemah suci yang diperintahkan Allah kepada Musa untuk dibangun menjadi tempat Tuhan berdiam di antara umat-Nya, bersekutu dan berkomunikasi dengan umat-Nya. Sekarang ini, orang percaya menjadi tempat kediaman Allah sehingga hadirat Tuhan yang kudus ada di antara umat-Nya. Tabernakel menunjuk pada pola ibadah yang ditentukan Tuhan bahkan menjadi pola pertumbuhan iman orang percaya. Metode yang digunakan ialah kualitatif. Tujuan penelitian ini adalah untuk mengetahui apa yang dimaksud dengan tabernakel dihubungkan dengan liturgi ibadah dan dampaknya serta pertumbuhan iman menurut tabernakel yang dirohanikan. Hasil analisis dan kajian menunjukkan bahwa ibadah yang berpola pada tabernakel akan adanya manifestasi Roh Kudus lewat karunia-karunia Roh Kudus. Kesimpulan penelitian ini, bahwa: ibadah berpola pada tabernakel akan memotivasi untuk meningkatkan pertumbuhan iman jemaat, gembala semakin percaya dengan panggilannya dan masih adanya manifestasi Roh Kudus lewat karunia-karunia Roh Kudus.